Cancer cell growth and survival as a system-level property sustained by enhanced glycolysis and mitochondrial metabolic remodeling - Alberghina, Lilia; Gaglio, Daniela; Gelfi, Cecilia; Moresco, Rosa M.; Mauri, Giancarlo; Bertolazzi, Paola; Messa, Cristina; Gilardi, Maria C.; Chiaradonna, Ferdinando; Vanoni, Marco (Frontiers in Physiology, 2012)
Systems Biology holds that complex cellular functions are generated as system-level properties endowed with robustness, each involving large networks of molecular determinants, generally identified by ”omics” analyses. In this paper we describe four basic cancer cell properties, that can easily be investigated in vitro: enhanced proliferation, evasion from apoptosis, genomic instability, inability to undergo oncogene-induced senescence. Focusing our analysis on a K-ras dependent transformation system, we show that enhanced proliferation and evasion from apoptosis are closely linked, and present findings that indicate how a large metabolic remodeling sustains the enhanced growth ability. Network analysis of transcriptional profiling gives the first indication on this remodeling, further supported by biochemical investigations and metabolic flux analysis. Enhanced glycolysis, down-regulation of TCA cycle, decoupling of glucose and glutamine utilization, with increased reductive carboxylation of glutamine, so to yield a sustained production of growth building blocks and glutathione, are the hallmarks of enhanced proliferation. Low glucose availability specifically induces cell death in K-ras transformed cells, while PKA activation reverts this effect, possibly through at least two mitochondrial targets. The central role of mitochondria in determining the two investigated cancer cell properties is finally discussed. Taken together the findings reported herein indicate that a system-level property is sustained by a cascade of interconnected biochemical pathways, that behave differently in normal and in transformed cells.